Sovereign Authority and the Limits of Constitutional Democracy - Trevor Allen Purvis (Oñati Socio-Legal Series)
The victory of Justin Trudeau’s Liberals in the Canadian federal election of 2015 brought with it hopes for meaningful change in the relationship between indigenous peoples and settler-Canadian society, with “reconciliation” a prominent feature of the new government’s discourse. But long on symbolism, the new government’s efforts have been markedly short on substance, and all good intentions seem unlikely to dislodge the more stubborn problems underpinning the relationship between indigenous peoples and the settler state that claims sovereignty over their lives. While many of the obstacles to be confronted involve familiar problems confronting institutional reform, deeper, more substantive barriers lie in the character of modern nation-formation and state sovereignty, and in contradictions that lie at the very heart of liberal constitutional democracies.